Aspergillus Contamination in Healthcare Facilities: An Ever-Present Issue—Prevention and Control Measures - Anna Maria Spagnolo (Hygiene)
Aspergillus spp. are ubiquitous fungi present in soil, organic debris, water, decaying vegetation and dust produced in renovation and/or building work. Several studies have shown the presence of aspergilli in various healthcare environments. Typically, thousands of fungal spores are inhaled every day, but if spore clearance fails (typically in immunocompromised patients), fungi can grow and invade lung tissue, causing invasive aspergillosis (IA) which is one of the most frequent infections in highly immunocompromised patients. Aspergillus fumigatus is the most common species involved; this species can be attributed to about 80% of the cases of aspergillosis. According to the WHO, Aspergillus fumigatus is one of four critical priority fungi. The first-line treatment of diseases caused by Aspergillus, in particular IA, is based on triazole antimycotics. Unfortunately, resistance to antimycotics is increasing, partly due to their widespread use in various areas, becoming a significant concern to clinicians who are charged with caring for patients at high risk of invasive mycoses. A recent WHO report emphasised the need for strategies to improve the response, and in particular strengthen laboratory capacity and surveillance, support investment in research and strengthen public health interventions for the prevention and control of fungal infections through a One Health approach.